Primary Care Providers' Barriers and Adherence to the United States Preventive Services Task Force (USPSTF) Mammography Screening Guidelines - Campbell, Marie (My University, 2015)
Earlier detection through mammography screening, increased awareness, and improved treatment modalities has resulted in a decline in breast cancer incidence. Despite the availability of the clinical guidelines by the United States Preventive Services Task Force (USPSTF), adherence to these methods is only 42% (Meissner et al., 2012). The purpose of this scholarly project was to identify and improve provider’s adherence to the USPSTF mammography screening clinical guidelines in three primary care clinics located in Southeastern North Carolina. The project included development of an educational program to increase awareness of the guidelines followed by measures to increase screening such as post cards, pink ribbon stickers for laptop computers, pink flyers for exam rooms, and email reminders. A post chart review was completed to determine if there was an increase in adherence and utilization of the guidelines following an educational intervention. The sample size included 90 retrospective chart reviews of the patients meeting the criteria for mammography screening. Based on the results of the retrospective chart reviews, further recommendations were provided to the providers to improve adherence. Data analysis was conducted using descriptive statistics. The findings of this project identified time commitment, IT reminders, lack of communication between primary care providers, lack of wellness visits, lack of time, lack of consistency with ordering mammograms, and lack of knowledge of how to use the electronic medical record preventive screening tool, as barriers to the adherence of the USPSTF mammography screening guidelines among primary care providers in three clinics located in Southeastern North Carolina. The educational intervention increased the adherence of the USPSTF mammography screening guideline from 15% to 16%.
Keywords: Barriers; Adherence; USPSTF; United States Preventive Services Task Force; Mammography screening guidelines